2017
DOI: 10.1017/s0305741017000935
|View full text |Cite
|
Sign up to set email alerts
|

Centralizing Trends and Pollution Law Enforcement in China

Abstract: This article analyses centralizing trends that may be able to reduce the negative influence of local protectionism on environmental law enforcement in China. The article finds that as centralizing trends unfolded, enforcement over time has become stricter and more frequent, however with only minor effects in reducing pollution. Moreover it finds a situation of uneven enforcement with richer and more urbanized areas having much stronger and more frequent enforcement than inland areas. Centralizing trends may th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 36 publications
4
45
0
Order By: Relevance
“…While inadequate enforcement in these policy areas are often attributed to the local government, this research suggests that the political concerns of high-level officials and especially the regime's central elites may also affect enforcement outcomes, a finding in line with the emphasis by some recent studies of the importance of "bringing the centre back" to fully understand the central-local dynamics in China's multi-level governance environment (e.g. Kostka and Nahm, 2017;Ran, 2017;van Rooij et al, 2017;…”
Section: Resultssupporting
confidence: 79%
“…While inadequate enforcement in these policy areas are often attributed to the local government, this research suggests that the political concerns of high-level officials and especially the regime's central elites may also affect enforcement outcomes, a finding in line with the emphasis by some recent studies of the importance of "bringing the centre back" to fully understand the central-local dynamics in China's multi-level governance environment (e.g. Kostka and Nahm, 2017;Ran, 2017;van Rooij et al, 2017;…”
Section: Resultssupporting
confidence: 79%
“…This article finds that all the non-pilot cities that have voluntarily enacted HSW sorting decrees are from richer regions in China (see Section 2.2.1. ), which supports the existing studies which suggested that richer localities where conflicts between economic and environmental interests were less likely to arise, had more interest in improving environmental governance [18].…”
Section: Some Localities Do Show Positive Attitudes Toward the Nationsupporting
confidence: 88%
“…Some analyzed the air policies of Hangzhou, one of the main cities in eastern China and found that Hangzhou has made institutional innovations to support the national environmental goals, casting doubt on the rough division between "national level effective/local sabotage" [17]. In the context of pollution regulation enforcement, research showed that richer regions whose economic and environmental interests were less likely to be in conflict were more supportive of national environmental policy [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the continued broadening and deepening of plans, the leadership has launched governance reforms that reinforce the dominant governance processes through strengthened and centralized environmental enforcement in which the Party directs and oversees implementation (Kostka & Nahm, ; Kostka & Zhang, ; Van Rooij, Zhu, Li, & Wang, ). Two important new mechanisms initiated by the party/central government are the national environmental supervision system ( zhongyang huanbao ducha ) and vertical management reforms in the environmental bureaucracy, both launched in 2016.…”
Section: The Power Of Institutionalized Governance Processesmentioning
confidence: 99%